Ne s nami - Sigalaeva, Svetlana (Russia, 2012)
A personal view of a previously-hidden aspect of Russian LGBT culture: the surprisingly supportive and uniquely familial community which develops within a women’s prison. This unique brand of LGBT culture is viewed through the eyes of a recently-released inmate.
Verzio Film Festival Submission